Implementasi Pengungkapan Environmental, Social dan Governance Terhadap Kinerja Keuangan: Studi Empiris pada Perusahaan Sektor Keuangan yang Terdaftar di BEI Periode: 2021 -2023 - Atria Dea Permata; Erma Setiawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
the purpose of this study was to axamine the influence of environmental, social, and governance disclosure on the company performance. This study uses quantitative research methods with purposive sampling method as a sampling technique. The sample of this study is finance sector company listed on the Indonesia Tock Exchange in 2021-2023 and obtained 26 firms as samples that match the criteria. This study uses secondary data obtained from the company’s annual report and sustainibillity report using the documentation method. Hypothesis testing was carried out using multiple linear regression analysis methods. The result of this study indicate that environmental and governance have an influence on company performance. Meanwhile, the social have no influence on company performance.